The application of bowen's family system theory (BFST) to the malay population in Malaysia - Raba'aton Adawiah Mohd Yusof (Queensland University of Technology, 2012)
The rapid economic development and social changes in Malaysia recently have led to many psychosocial problems in young people, such as drug addiction, child sexual abuse and mental illness. The Malaysian government is beginning to focus more attention on its social welfare and human service needs in order to alleviate these psychosocial problems.